P3.341 Sex and the London Olympics 2012 Part 1. Impact on Community Sexual Health Service Provision in London. (13th July 2013) - Brook, G; Cassell, J; Mercer, C; Coyne, K; Maguire, H; Hughes, G; Crook, P
Abstract : Background: Predicting the impact on services is essential for managing large public events. Objectives: To measure the impact of the 2012 Olympics on service use in London Methods: Data were gathered from London sexual health services in London for July-September 2012 relating to contraception, sexual assault, sex worker services and telephone sexual health advice Results: Emergency contraception prescriptions rose by 20% (from 1086 to 1353) over the Olympic and post-Olympic period as compared to the previous month. In the Brook London contraception clinics there was a 9% rise (from 1209 to 1328) in all attendance over the Olympic period as compared with 2011. In the three main sexual assault services, 1–7% of reported incidents were in clients who were visiting the Olympics. In a survey of 102 sex workers, 59% (59/102) reported fewer clients and 46% (46/102) reported more police interference and brothel closures. Sixteen (16%) were new sex workers and 7% (7/102) came to London specifically for the Olympics. Telephone advice line calls about sexual health fell by 19% (from 741 in the previous month to 622 over the Olympics) then rose by 25% (from 622 to 828) in the month after the Olympics. This increase was mainly due to calls by women with vaginal symptoms (from 112 to 184, 61% increase) and urinary tract problems (from 150 to 223, 67% increase). Conclusions: Contraception service use was higher and emergency contraception prescriptions increased following the Olympics. Reported use of sexual assault services, sex workers and telephone advice was low during the Olympics but there was a large rise in requests for sexual health advice afterwards. These data will prove valuable in planning sexual health service provision for cities with large-scale events in the future